2018
DOI: 10.2139/ssrn.3178692
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment and Online Labor

Abstract: Online labor markets experienced a rapid growth in recent years. They allow for long-distance transactions and offer workers access to a potentially 'global' pool of labor demand. As such, they bear the potential to act as a substitute for shrinking local income opportunities. Using detailed U.S. data from a large online labor platform for microtasks, we study how local unemployment affects participation and work intensity online. We find that, at the extensive margin, an increase in commuting zone level unemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Online labor markets have become increasingly popular in recent years (Difallah et al 2015), with 0.5% of the US adult population working in the "sharing economy" in 2016 ( 2017). For many workers, these jobs serve as a substitute for traditional offline work in times of economic downturn (Borchert et al 2018). For them, online labor markets are a regular work environment, which makes it a perfect testbed to study volunteering at the workplace.…”
Section: Workers and The Online Labor Marketmentioning
confidence: 99%
“…Online labor markets have become increasingly popular in recent years (Difallah et al 2015), with 0.5% of the US adult population working in the "sharing economy" in 2016 ( 2017). For many workers, these jobs serve as a substitute for traditional offline work in times of economic downturn (Borchert et al 2018). For them, online labor markets are a regular work environment, which makes it a perfect testbed to study volunteering at the workplace.…”
Section: Workers and The Online Labor Marketmentioning
confidence: 99%
“…Indeed, Borchert et al (2018) have found that unemployment shocks, leading to increased participation in online markets, can have a positive effect on wage elasticities in crowdwork.…”
Section: Discussionmentioning
confidence: 99%
“…Dube et al (2018) address monopsony in online labour markets, finding that their peculiar structure allows platforms to impose a considerable markup on workers' productivity, leading up to a 20% contraption in their earnings. Looking at the supply of online workforce, the relationship between unemployment and micro-task labour markets was further explored in Borchert et al (2018), where labour demand shocks have been found to affect temporary participation in online labour markets. Negative spill-over effects from crowdwork markets may be less obvious, but cannot be excluded.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the economic maturation of online freelance platforms, regional markets emerged, driven by language barriers and buyers’ preference to satisfy their demand for labour domestically (Borchert et al, 2018). Two of the largest regional submarkets shaped by language and domestic demand, outside of the global, English-language domain, are Spanish- and Russian-language freelance domains.…”
Section: New Features Of the Online Labour Index 2020mentioning
confidence: 99%